Implementation of PBL Model with Ethnomathematical Nuances on Mathematical Problem-Solving Ability Reviewed from Confidence - Dwi Arifa; Zaenuri Zaenuri (Universitas Negeri Semarang, 2026)
This study aims to analyze the effectiveness of the application of the Problem Based Learning (PBL) model with ethnomathematical nuances in improving mathematical problem-solving skills and examining the role of students' confidence. This study uses a mixed method with the design of the Contol Group Posttest. The population in this study is all students of class XI of SMA Negeri 6 Semarang. The research sample consisted of two classes XI of SMA Negeri 6 Semarang which were selected based on the cluster random sampling technique, with the provision of one experimental class with treatment and one control class. The instruments used included a test of problem-solving ability based on Polya's steps, a confidence questionnaire, and interview guidelines. Data were analyzed using SPSS. The results of the analysis prerequisite test showed that the data was normally distributed and had a homogeneous variance. The one-sample t-test resulted in an average experimental class score of 87.36 which is significantly higher than the KKM in schools of 75 with a significance value of 0.000. The independent sample t-test showed a significant difference between the experimental class and the control class, thus emphasizing that the application of the PBL model with ethnomathematical nuances was effective in improving mathematical problem-solving ability. Based on the results of the analysis of the percentage of questionnaire indicators and interviews with students, results were obtained at a high level of confidence, showing more optimal problem-solving achievement compared to students with medium and low levels of confidence. The results of this study show that the ethnomathematical PBL model not only has a significant impact on improving students' ability to solve mathematical problems, but also contributes to increasing students' confidence.